1995
DOI: 10.1007/bf00010290
|View full text |Cite
|
Sign up to set email alerts
|

Metal distribution across different pools in the organic layer of a forest under acid deposition and its consequences for the metal dynamics

Abstract: Metal distribution across disfferent pools in the organic layer of a forest under acid deposition and its consequences for the metal dynamics Wessel, W.W.; Tietema, A. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…2,3 CEC, defined as a maximum number of adsorbed ions held per kg of dry soil, is an important parameter for estimating cation retention and losses from soils. 3 Of particular importance for soil processes are exchangeable base cations (Na, K, Ca, Mg), which are related to soil buffering capacity, 4,5 plant nutrition [6][7][8] and soil solution quality control. 9 Base saturation (the percentage of equivalent sum of base cations in CEC ) of soils determines the influence of exchange complex on soil solution chemistry and is an important parameter for estimating cation retention and losses from forest soils.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 CEC, defined as a maximum number of adsorbed ions held per kg of dry soil, is an important parameter for estimating cation retention and losses from soils. 3 Of particular importance for soil processes are exchangeable base cations (Na, K, Ca, Mg), which are related to soil buffering capacity, 4,5 plant nutrition [6][7][8] and soil solution quality control. 9 Base saturation (the percentage of equivalent sum of base cations in CEC ) of soils determines the influence of exchange complex on soil solution chemistry and is an important parameter for estimating cation retention and losses from forest soils.…”
Section: Introductionmentioning
confidence: 99%
“…2). This indicated that the water-soluble fraction of these elements in the litter forms a substantial part of the total amount in the litter (Wessel and Tietema 1994). Profound initial leaching of K has been found in many litterbag studies (Gosz et al 1973);Yavitt and Fahey 1986).…”
Section: Discussionmentioning
confidence: 91%
“…Amounts of NH 4 + and/or NO 3 -added (Table 2) were calculated from the amounts of nitrogen added to the forest floor during a rain event (2.7 kg-N ha -1 ; Hansen et al 1994;Raat et al 2002), the molar ratio of NH 4 + :NO 3 -in throughfall (2.7:1; Draaijers et al 1998) and the total dry mass of the forest floor (3.2 kg m -2 ; Wessel and Tietema 1995). In this calculation we assumed that throughfall was distributed evenly over the top half of the forest floor.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…Secondly, even in the WD incubations, about half of the NO 3 -net produced was transformed into N 2 O, denoting the relative importance of denitrification in exporting NO 3 -from the LF1 horizon. The contribution of both sinks to the total N balance of the Speuld forest, however, remains relatively small as dry mass of the LF horizon is only 12% of the total dry mass of the forest floor (Wessel and Tietema 1995). Rough estimates demonstrate that the maximum loss of NO 3 -via incorporation into DON or loss as N 2 O is about 1 kg-N ha -1 yr -1 for each NO 3 -sink, respectively, which is small compared to the 31 kg-N ha -1 yr -1 of NO 3 -that are leached from the soil at 90 cm depth.…”
Section: N 2 O Production Potential In Fresh Littermentioning
confidence: 99%